Brand loyalty on sport shoes purchase : a Malaysian perspective - Chong, Justin (2000)
Many researchers focus on the issue of branding even though it is not one of the important 4 Ps we learn in marketing. The study was conducted with the main objective of examining the effect of the elements of cognitive and subjective norm and their impact on brand loyalty on sport shoes. The secondary objective was to identify whether there are significant differences between ethnic groups with regard to brand loyalty on sports shoes. Based on the literature, a set of 3 page questionnaire was designed. The current high growth areas of Kuala Lumpur, Petaling Jaya, Cheras, Serdang and Kajang in the state of Selangor Darul Ehsan were selected for sampling. Using the field approach, a survey was conducted over two weeks during the second half of November 2000, involving 180 respondents. The results indicated that the cognitive and subjective norm elements did have a positive effect on brand loyalty. Of the five elements of cognitive studied; awareness, reputation, image, perceived quality and satisfaction; had greater impact on brand loyalty. The study also shows there are significant difference between ethnic groups for sport shoes brands of Adidas, Puma, and Power; while Nike and Reebok show no significant differences. In summary, the study calls for greater attention to be given to branding especially in developing brand loyalty in Malaysia. The study also highlights the important of cognitive elements in its role as the main cause of brand loyalty.